Broadening the Scope of Craft Teaching: Exploring Out-of-School Teaching Practices - Kokko, Sirpa; Väänänen, Niina (FormAkademisk, 2023)
The focus of Finnish craft teacher education is on educating craft teachers in formal basic education. In this study, the aim was to research craft student teachers’ experiences of teaching practices that were arranged in out-of-school contexts. The data comprised craft student teachers’ (n = 18) written reflections included in their course portfolios. Their teaching practice took place in adult education centres, basic education in arts, older peoples' care homes, youth work centres, centres for people with disabilities, social work centres, museums, craft cafés and clubs and a vocational training institution. The written reflections concerned the students’ expectations at the beginning and those at the end of the teaching practice and were analysed according to the principles of qualitative data analysis. The students found both similarities and differences in craft pedagogy in different contexts. The out-of-school teaching practice broadened their future career perspectives and equipped them with new pedagogical skills.